1999
DOI: 10.2355/isijinternational.39.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen on Formation of Martensite-Austenite Constituent in Low Carbon Steels.

Abstract: (Ti-Low. Ti-High) were microalloyed wlth two levels of titanium while the base composition was kept constant and the total nitrogen level maintained at I 10 ppm.The steel cornpositions are shown in Table 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…22) In contrast, in agreement with the results shown in Fig. 5, steel 11VN has lower hardenability after schedule B, mainly due to the effect of accumulated strain.…”
Section: Pearlite Microstructuresupporting
confidence: 88%
See 1 more Smart Citation
“…22) In contrast, in agreement with the results shown in Fig. 5, steel 11VN has lower hardenability after schedule B, mainly due to the effect of accumulated strain.…”
Section: Pearlite Microstructuresupporting
confidence: 88%
“…21) It is worth emphasizing that Staiger et al observed a similar effect when nitrogen content increased from 30 to 70 ppm in the formation of hard constituents in the case of low carbon wire-rods. 22) In contrast, in agreement with the results shown in Fig. 5, steel 11VN has lower hardenability after schedule B, mainly due to the effect of accumulated strain.…”
Section: Pearlite Microstructuresupporting
confidence: 88%
“…When observing the PM at high magnification under SEM, the dark color regions appear to constitute of M–A constituents and degenerate pearlite ( Figure 7 c). M–A constituents are formed because of austenite stabilizing elements, such as manganese and nickel, that allow austenite to exist at room temperature [ 49 ]. Note in Table 1 , the as-received X70 PM contains some nickel, a strong austenite stabilizer [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was found for a soak temperature of 1200 o C, fig. 5b.The actual mechanism for N lowering the transformation is not fully understood, but it has been suggested [9] that nitrogen may hinder nucleation or growth of the pearlite reaction by interfering with diffusional processes or that N rapidly partitions to the last transforming austenite, increasing hardenability. · Specimens experiencing complete transformation prior to coiling have a well-defined dilation trough and peak, indicating the temperature region where the bulk of the transformation occurs.…”
Section: Influence Of C and N On Transformation: I N O R D E R T O E mentioning
confidence: 99%